Implementation and validation of a Dynamic Net Present Value (DNPV) for calculating financial return in oil reservoirs (Research, Society and Development, 2024)
Net Present Value (NPV) is recognized as a fundamental and widely adopted metric in the financial analysis of oil exploration projects, given that extraction from a well is not carried out until the resource is exhausted, but rather, as long as it is economically viable. Due to the volatility of oil prices, the decision to shut down a well, even when it still contains oil, becomes a reality when extraction and maintenance costs outweigh profits. Although Net Present Value (NPV) has been extensively studied in Reservoir Engineering literature, a common simplification is observed when employing a fixed Minimum Acceptable Rate of Return (MARR) and operational costs. Therefore, this article aims to present the development and application of a methodology for implementing a variable NPV, here named as Dynamic NPV (DNPV), used in the area of oil and gas well exploration. This new methodology presents three contributions: first, a variable MARR according to Brazil's risk-free interest rate (Selic Rate); second, all variable costs are updated by the Brazilian IGP-M index, which is used to adjust the price of a barrel of oil; third, the use of all types of exploration well drilling (vertical, horizontal, and directional). To verify the efficiency of the proposed DNPV, its calculation was applied to real data, showing an accuracy rate of over 97% in the decision to maintain or shut down an oil well according to its profitability, as measured by the DNPV.